The Importance of Domestic Space in the Times of COVID-19 - Marco Aresta; Nikos A. Salingaros (Challenges, 2021)
This essay discusses a deep malaise of contemporary architecture, made more obvious by experiencing COVID-19 lockdowns for several months. Evidence-based arguments urge society to improve human health and well-being by re-considering the design of interior and exterior spaces. So far, predictions of how design will “improve” after COVID-19 just continue business-as-usual, ignoring accumulated evidence. Yet, the negative emotional experience of families cooped up during the pandemic reveals the failure of the standard approach to designing spaces. An architecture that adapts to human biology and psychology starts with the relatively new understanding of people interacting unconsciously with their environment and broadens it. A traditional design toolkit, augmented by the latest technology, can generate healing spaces as judged by their ability to enhance users’ subjective well-being. We recommend implementing specific design innovations to achieve this goal—replacing industrial-minimalism with biophilic and neuro-based design and using documented patterns that trigger feelings of happiness in users.